Catestatin Protects Against Diastolic Dysfunction by Attenuating Mitochondrial Reactive Oxygen Species Generation - Zeping Qiu; Yingze Fan; Zhiyan Wang; Fanyi Huang; Zhuojin Li; Zhihong Sun; Sha Hua; Wei Jin; Yanjia Chen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Catestatin has been reported as a pleiotropic cardioprotective peptide. Heart failure with preserved ejection fraction (HFpEF) was considered a heterogeneous syndrome with a complex cause. We sought to investigate the role of catestatin in HFpEF and diastolic dysfunction. METHODS AND RESULTS Administration of recombinant catestatin (1.5 mg/kg/d) improved diastolic dysfunction and left ventricular chamber stiffness in transverse aortic constriction mice with deoxycorticosterone acetate pellet implantation, as reflected by Doppler tissue imaging and pressure‐volume loop catheter. Less cardiac hypertrophy and myocardial fibrosis was observed, and transcriptomic analysis revealed downregulation of mitochondrial electron transport chain components after catestatin treatment. Catestatin reversed mitochondrial structural and respiratory chain component abnormality, decreased mitochondrial proton leak, and reactive oxygen species generation in myocardium. Excessive oxidative stress induced by Ru360 abolished catestatin treatment effects on HFpEF‐like cardiomyocytes in vitro, indicating the beneficial role of catestatin in HFpEF as a mitochondrial ETC modulator. The serum concentration of catestatin was tested among 81 patients with HFpEF and 76 non–heart failure controls. Compared with control subjects, serum catestatin concentration was higher in patients with HFpEF and positively correlated with E velocity to mitral annular e′ velocity ratio, indicating a feedback compensation role of catestatin in HFpEF. Conclusions Catestatin protects against diastolic dysfunction in HFpEF through attenuating mitochondrial electron transport chain–derived reactive oxygen species generation. Serum catestatin concentration is elevated in patients with HFpEF, probably as a relatively insufficient but self‐compensatory mechanism.